Improved Masticatory Performance in the Partially Edentulous Rehabilitated with Conventional Dental Prostheses - Maria Angeles Lopez-Cordon; Laura Khoury-Ribas; Bernat Rovira-Lastra; Raul Ayuso-Montero; Jordi Martinez-Gomis (Medicina, 2024)
Background and Objectives: Oral rehabilitation seeks to enhance mastication, a vital component of oral function that is compromised by tooth loss. This study aimed to assess the degree of improvement of masticatory performance in partially edentulous patients rehabilitated with removable partial dentures (RPD) or fixed partial dental prosthesis (FPDP). Changes in the occlusal contact area (OCA) and satisfaction with their chewing ability during the adaptation period were also evaluated. Materials and Methods: in total, 34 partially edentulous participants (median age 65.3 years; 56% women) who received an RPD or FPDP were assessed using masticatory performance assay, OCA calculation, and a visual analog scale (VAS). Results: Masticatory performance improved by 20% (range from 17% to 25%, p < 0.05) depending on the edentulism and the rehabilitation types. The OCA improved by 4.7 mm2 (p < 0.05) and satisfaction with the masticatory function improved by 9% (p < 0.05) 3 months after prosthesis insertion. Conclusions: Conventional prostheses benefited partially edentulous individuals, improving masticatory performance by 20%. Treatment also increased the OCA in all types of partial edentulism, except in Kennedy class I patients rehabilitated with RPD. Patients’ satisfaction with their chewing ability only increased in Kennedy class III patients rehabilitated with RPD.